The Effect of Socioeconomic Factors and Financial Knowledge on The Financial Literacy of Generation Z at SMK PAB 2 Helvetia - Ahmad Fadlan; Suhendi, Suhendi; Widya, Atika (Universitas Dehasen Bengkulu, 2025)
This study aims to analyze the impact of socioeconomic factors and financial knowledge on the financial literacy of Generation Z at SMK PAB 2 Helvetia. This research uses a quantitative method with a descriptive and explanatory approach to measure and analyze the influence of two independent variables on the dependent variable. The population in this study consists of all Generation Z students at SMK PAB 2 Helvetia, ranging from grade X to grade XII. The sample consists of 100 respondents selected randomly and meeting the research criteria. Data collection was conducted through a survey method with a questionnaire distributed to the selected students. The results of the study indicate that socioeconomic factors have a significant effect on financial literacy, while financial knowledge does not show a significant impact on financial literacy among Generation Z at SMK PAB 2 Helvetia. These findings highlight the importance of socioeconomic factors in improving financial literacy among students, while financial knowledge requires a more in-depth approach in its teaching.